PERUBAHAN TUTUPAN LAHAN DI HUTAN KEMASYARAKATAN GAPOKTAN JAYA LESTARI PROVINSI LAMPUNG - Fredy Rahmandani; S. B. Yuwono; C. Wulandari (Lambung Mangkurat University-Indonesia, 2021)
The research, which was conducted at the Gapoktan HKm Jaya Lestari at the Bukit Punggur KPH, aimed to find out changes in land cover in the HKm work area in 2000, 2009 and 2017, and to determine the effect of the implementation of the HKm program on the condition of forest cover in these locations. This research data analysis used Geographic Information Systems (GIS). Image data analysis includes analysis of land changes carried out by identifying changes in objects in different images at the study site. The extent of each class was calculated from all image data series (2000, 2009 and 2017), then interpretation through descriptive data analysis. Based on the results of this study, the period 2000-2009 added the largest area of land cover in the Secondary Dry Land Forest (Hs) class (1.34% to 83.56%). The addition occurred due to a decreasing in the area of dryland agriculture cover (Pt) 55.48%, Open land (T) 12.91%, Primary dry land forest (Hp) 6.57%, Settlement (Pm) 4.95%, and shrubs (B) 2.34%. The 2009-2017 period of forest land cover which experienced the biggest change was the secondary dryland forest class (Hs), which experienced a decrease in area (83.56% to 46.08%) then primary dryland forest (HP) 7.06%, compared to inverted with settlement class (Pm) which increased 2.69%, followed by shrubs (B) 24.71%, open land (T) 20.56%, and dry land Agriculture (Pt) 3.54%. This provides an important finding and is based on the results of scientific analysis that the land cover in the form of forest trees in the area of Gapoktan management is reduced after the IUP-HKm is accepted by the community. It can be seen from the amount of additional cover in the form of shrubs, settlements and open land. Based on these conditions it is necessary to make efforts to improve the management system of HKm Gapoktan Lestari Jaya area through an agroforestry program.